Nonautoimmune congenital hyperthyroidism due to p.Asp633Glu mutation in the gene - Won Kyoung Cho; Moon-Bae Ahn; Woori Jang; Hyojin Chae; Myungshin Kim; Byung-Kyu Suh (Korean Society of Pediatric Endocrinology, 2018)
Most cases of congenital hyperthyroidism are autoimmune forms caused by maternal thyroid stimulating antibodies. Nonautoimmune forms of congenital hyperthyroidism caused by activating mutations of the thyrotropin receptor (TSHR) gene are rare. A woman gave birth to a boy during an emergency cesarean section at 33 weeks of gestation due to fetal tachycardia. On the 24th day of life, thyroid function tests were performed due to persistent tachycardia, and hyperthyroidism was confirmed. Auto-antibodies to TSHR, thyroid peroxidase, and thyroglobulin were not found. The patient was treated with propylthiouracil and propranolol, but hyperthyroidism was not well controlled. At 3 months of age, the patient had craniosynostosis and hydrocephalus, and underwent a ventriculoperitoneal shunt operation. Direct sequencing of the TSHR gene showed a heterozygous mutation of c.1899C>A (p.Asp633Glu) in exon 10. No mutations were discovered in any of the parents in a familial genetic study. We have reported a case of sporadic nonautoimmune congenital hyperthyroidism, by a missense mutation of the TSHR gene, for the first time in South Korea.